Measuring barriers to access financial services in east java, Indonesia: a Confirmatory Factor Analysis (CFA) - Abdul Razak, Dzuljastri; Maulana, Hartomi; Adeyemi, Adewale Abideen (2017)
Even though the banking industry is growing exponentially, they are still out of reach of the hardcore poor. The population under poverty remains financially excluded from the mainstream banking facilities. The aim of this paper is to empiricallyexamine the main factors that hinder customers to access financing from mainstream banking in Indonesia’s province of East Java using confirmatory factor analysis (CFA). The paper employs primary data collected by self-administered questionnaires involving a sample of 243 respondents from five different regencies in East Java. A CFA techniques were used on the hypothesized model with five latent variables, namely religious, affordability, accessibility eligibility, availability factors.